A methodology to assess cultural geo-resources: Encouraging geotourism in Tierra del Fuego (Southern Patagonia, Argentina) - Schwarz, Soledad Natalia (2022)
This contribution aims to present a methodology to select, describe and hierarchize cultural georesources in northern Tierra del Fuego (Argentina) in order to encourage geotourism strategies in this touristically underdeveloped area. A cultural georesource refers to a geological or geomorphological site which reveals an archaeological or historical record related to the regional peopling. Based on previous own papers about methodologies to assess geodiversity, an specific approach that adds a cultural viewpoint of georesources is inhere presented. The analysis is based on three axis: geological/geomorphological, cultural and tourist aspects, considering six criteria with four parameters in each case, as follows: Geological/geomorphological criteria: available information, preservation degree, singularity, representativeness, didactic interest and degradation risk. Cultural criteria: available information, frequency, chronology, preservation degree, vulnerability and didactic interest. Tourist criteria: scenic value, complementarity of natural and cultural elements, current land uses, tourist development strategies, facilities and accessibility. Each criteria is weighted according to a scale from 0 to 3, being 3 the best rated. The sum of the eighteen parameters’ values gives a final score to each cultural georesource. This methodology was applied on 48 geological or geomorphological sites previously detected, through almost 380 km along coastal and inland roads. 27 of them turned out to be cultural georesources that were afterwards described, mapped and hierarchized in different landscapes of northern Tierra del Fuego, such as Holocene fluvial, littoral, lacustrine and aeolian environments, Pleistocene moraines and Miocene rocky hills. At the same time, these georesources contain information about different stages of peopling from pedestrian hunters gatherers since 7000 yrs B.P., the European arrival during the XIXth century until the settlement of the present economic activities which include cattle rising and oil industry. Besides, most cultural georesources offer no facilities, some of them are not even free to access and just a few, mainly those close to urban areas, are already being used for recreational purposes. For instance, the best cultural georesource rated in this study is “Río Grande estuary” with 41 points over the maximum of 54. Located close to a main Fuegian city, it is a great example of fluvial-littoral processes and a keystone of recent history. However, it is not included in the current tourist offer but this condition could change taking into account this type of research which draws upon the educational potential. The methodology proved to be useful as a tool to assess georesources considering their cultural values. This approach allows to deepen the understanding of the local history in terms of natural and cultural processes, since it focuses on the didactic interest of each resource. This may lead to reinforce the local identity as well as to spread Earth and Human Sciences in site sceneries in a more attractive way